2015
DOI: 10.1111/fcp.12137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of corticosteroids on articular cartilage: have animal studies said everything?

Abstract: Intra-articular (IA) corticosteroids (CS) have been used in the treatment of osteoarthritis for many years, although their effects on articular cartilage are not fully understood. To identify whether previous animal studies have provided enough evidence about the effects of CS, we undertook a systematic review that identified 35 relevant in vivo animal experimental studies between 1965 and 2014 assessing the effects of CS on either normal cartilage, or in either induced osteoarthritis (OA) or synovitis. The qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…Only five studies in the species were found, but none of them had shown a real efficacy of the product in reduction of clinical signs. Some of those authors conducted another systematic review (Vanderweerd et al, 2015) to evaluate the effect of corticosteroids in healthy joints, and with osteoarthritis/synovitis induced experimentally. The investigation was conducted in rabbits, dogs and horses, and the evaluation period was from 1965 to 2014.…”
Section: Corticosteroids For Intra-articular Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Only five studies in the species were found, but none of them had shown a real efficacy of the product in reduction of clinical signs. Some of those authors conducted another systematic review (Vanderweerd et al, 2015) to evaluate the effect of corticosteroids in healthy joints, and with osteoarthritis/synovitis induced experimentally. The investigation was conducted in rabbits, dogs and horses, and the evaluation period was from 1965 to 2014.…”
Section: Corticosteroids For Intra-articular Treatmentmentioning
confidence: 99%
“…However, Céleste et al (2005) reported that intraarticular administration of four doses (12 mg/kg) of TA before and after (3, 5 and 7 weeks) arthrocentesis of horse's radiocarpal joints did not result in damage to the cartilage. On the other hand, according to Vanderweerd et al (2015), the real effect of the corticosteroids in the articular cartilage to be continued controversy, because many limitations in the methodology were found. Despite the satisfactory results of TA, Céleste et al (2005) reported that this steroid also presented a potential to alter the metabolism of cartilage, as evidenced by using biomarkers in SF of healthy horses after three doses of the drug in two-week intervals.…”
Section: Corticosteroids For Intra-articular Treatmentmentioning
confidence: 99%
“…The fast action of intra-articular CS injection is well recognized, however the long-term outcome of repetitive injections remains unknown (11). CS is able to block the synthesis and activation of matrix metalloproteinases, slowing down decomposition of the cartilage matrix (15,20). However, a repetitive high dose of CS can hinder the regeneration of articular cartilage by downregulating proteoglycan and HA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term use and a high frequency of injections of either agent may cause unnecessary injury and even infection in the arthritic joint. Furthermore, it has been reported that CS increases the apoptotic progression of cartilage cells when injected into the OA joint (15). Clinicians must therefore delicately balance the amount of CS used to avoid doing more damage than good.…”
Section: Introductionmentioning
confidence: 99%
“…However, other animal studies have had mixed results, and in some instances have shown beneficial effects on cartilage structure. 35 One study comparing triamcinolone acetonide injections to saline injections in the knee every 3 months for 2 years showed no difference in joint space loss. 36 …”
Section: Steroid Injectionsmentioning
confidence: 99%